Carboxyl terminus of Hsp70‐interacting protein (CHIP) is required to modulate cardiac hypertrophy and attenuate autophagy during exercise. (2nd April 2013) - Willis, Monte S.; Min, Jin‐Na; Wang, Shaobin; McDonough, Holly; Lockyer, Pamela; Wadosky, Kristine M.; Patterson, Cam
<x xml:space="preserve">Abstract</x> The carboxyl terminus of Hsp70‐interacting protein (CHIP) is a ubiquitin ligase/cochaperone critical for the maintenance of cardiac function. Mice lacking CHIP (CHIP−/−) suffer decreased survival, enhanced myocardial injury and increased arrhythmias compared with wild‐type controls following challenge with cardiac ischaemia reperfusion injury. Recent evidence implicates a role for CHIP in chaperone‐assisted selective autophagy, a process that is associated with exercise‐induced cardioprotection. To determine whether CHIP is involved in cardiac autophagy, we challenged CHIP−/− mice with voluntary exercise. CHIP−/− mice respond to exercise with an enhanced autophagic response that is associated with an exaggerated cardiac hypertrophy phenotype. No impairment of function was identified in the CHIP−/− mice by serial echocardiography over the 5 weeks of running, indicating that the cardiac hypertrophy was physiologic not pathologic in nature. It was further determined that CHIP plays a role in inhibiting Akt signalling and autophagy determined by autophagic flux in cardiomyocytes and in the intact heart. Taken together, cardiac CHIP appears to play a role in regulating autophagy during the development of cardiac hypertrophy, possibly by its role in supporting Akt signalling, induced by voluntary running in vivo. Copyright © 2013 John Wiley & Sons, Ltd.